La sociedad civil en Ecuador como agente del desarrollo: aportes y desafíos actuales (Estudios) - Cueva Quinde, Guido (2018)
Social organizations in Ecuador have determined their commitment within society to ensure the survival, reproduction and quality of life of human beings to develop specific lines of work. However, in 2007 there is an atmosphere of tension between those who exercise political power and organizations. This article describes and evaluates the contributions and challenges of the CSOs during the presidency of Rafael Correa, that is the context in which they have developed, the strengths and conflicts that they maintain for the daily exercise of their work as actors of the development of our country.